Alvaro Siza’s tectonic shift in Leça da Palmeira: from design to conservation - Ferreira, Teresa Sofia Faria Cunha (2021)
From 1958 to 1966, Álvaro Siza Vieira (Portuguese Architect, Pritzker Prize-winner in 1992) designed two paradigmatic works along the seafront in Leça da Palmeira, near Porto, in the north of Portugal: the Boa Nova Tea House (1958-1963) and the Ocean Swimming Pool (1959-1966). Although these projects were built on the same coastal road and were designed almost simultaneously, their tectonic principles are quite different: in the Tea House, Siza uses traditional materials mixed with modern ones, attempting to combine vernacular constructive elements with the use of modern technologies; on the contrary, in the Swimming Pool, the architect adopts a modern technology and an abstract neoplastic language. This tectonic shift can be explained by the evolution of the Portuguese architectural debate during the 1960s. Both buildings are now listed as National Monuments (2011) and have been included in the Portuguese Tentative List for World Heritage (2017). Furthermore, they have been subjected to recent interventions by Álvaro Siza himself (Tea House, 2013-2014; Swimming Pool, 2019-2020). Focusing on the technological and material legacies, this paper seeks to analyse the life cycle of these buildings, from their original design to their ageing process and transformations, including recent conservation work. Moreover, this paper also reflects on two different approaches to one of the most challenging issues in the conservation of modern architecture: concrete repair and its maintenance over time.